Diversity and Population Structure of Local Rice Varieties from Indonesia Revealed by SSR Markers - Rerenstradika Tizar Terryana; Puji Lestari; I Gusti Komang Dana Arsana; Kristianto Nugroho; I Made Jana Mejaya; Priatna Sasmita; Yudi Sastro; Karden Mulya; Dwinita Wikan Utami; Mastur (Bogor Agricultural University, Indonesia, 2022)
Indonesia's local rice varieties (Oryza sativa L.) have a wide range of diversity that can be valuable sources for crop improvement with molecular markers. This study investigated local rice varieties' genetic diversity and population structure using simple sequence repeat (SSR) markers. The SSR markers demonstrated their informativeness for genotypic characterization as represented by the gene diversity indices and polymorphic information content. The UPGMA dendrogram divided 63 varieties into two distinct clusters with different levels of sub-grouping and the tendency according to their origins, as supported by PCoA. In contrast, PCA of these varieties according to agro-morphological traits was scattered in all quadrants. Thus, DNA level variation analyzed by SSR seems to complement the phenotypic traits, which were not well structured and revealed significant genetic diversity among varieties, within, and among populations (P<0.01). The pattern of grouping structure analysis of total varieties into two subpopulations is similar to the dendrogram according to SSR markers but better resembles the pedigree information of the set local varieties. These findings have implied their importance in rice breeding for genetic improvement, maintenance, and management of local genetic resources in Indonesia.